Agregar al inciso 2 del art. 5 del COIP. El principio de favorabilidad no será aplicable para quienes sean reincidentes por el mismo delito - Farinango Morales, Edwin Edmundo (2016)
With the entry into force of the Code Criminal Integral (COIP), from August 10, 2014, there have been serious changes and modifications regarding the application of the law in criminal matters. Currently we have new procedures seeking to accelerate the proceedings and compliance with constitutional guarantees. One of the benefits clearly evidenced by this law; It is the principle of lenity offense under paragraph 2 of Article 5 of the Code of Criminal Integral (COIP). With the principle of lenity and pursuant to Record No. 288 of July 14, 2014, which was approved scales for illegal possession of narcotics. Nationally several people tried for the crime of drug trafficking gained their freedom, as this table does not sanctioned the micro traffic. In the years 2014 to 2015, with the previous scale approved by Resolution No. 002 CONSEP CD-2014 there were approximately 2232 released, 99% was serving sentences for drug for the release of detainees no criminal record that could be considered each detainee. The principle pro reo (favorability), aims to protect the citizen who is being investigated by the body of criminal prosecution and therefore it is subject of criminal law and such protection, in the light of this principle is aimed at seeking a solution more favorable to the existence of a conflict of laws, an event in which one should choose the least serious to the interests of the individual law. This has allowed since Aug. 10, 2014, hearings decriminalization in Units Judicial Criminal country are made that result in applying the principle of favorability, the defendants sentenced to imprisonment have benefited from rebates and persons indicted by prison have been released without fulfilling all the years established in the judgments. There are specific cases of people reached by the principle of lenity, who are repeat offenders, i have been arrested for illegal possession of narcotics several times. I have also evidenced by my work as a member of the police force, which in specific cases of those who benefited from the principle of lenity, are again in the streets somehow involved in the sale, distribution or trafficking. While our social state and constitutional, is based on respect, realization and protection of the rights and guarantees of own citizens, which has involved the search for limits on the exercise of the punitive power of the state, the lesser degree of harmfulness of the rights of citizens and the creation of principles aimed not only to be modulators of judicial and administrative action, but also to lay the foundations or pillars of the criminal proceedings. The principle criminal favorability has not been oblivious to this change and this has mainly evidenced when applying that principle in the criminal whose execution is permanent in time, questioning the garantista function as a modulator of judicial activity meant its application and giving way to overtake the punitive power of the state. Traditionally, it was understood that against the collision of laws or face regulatory changes, the law that prove to be more beneficial to the interests of the accused applied, which operated automatically, ie without compunction, being this not a benefit but a right of every citizen. The principle of lenity is one of those general principles of penal system from the constitutional orbit forms the structure of due process is oriented to the achievement of the purposes of our legal system and that system operators must go tool set procedural must be subjected to criminal procedural law techniques. But for this principle restrictions that guarantee the rights of the accused must exist, but to the community to ensure that criminals and prisoners are serving criminal conduct appropriate penalties. Since last August to this month, a considerable percentage of persons detained for illegal drug trafficking have been released, as can be evidenced in the Centers Deprivation of Liberty. It would be necessary to ask how many of these people have been rehabilitated and how many of these people exploiting the principle of favorability are again involved in illegal drug trafficking? In specific cases, who were released had convictions for selling marijuana in educational establishments, one of the major concerns we have had as cops is to protect the safety of teenagers and young people not involved in drugs. To correct and punish the micro traffickers who benefited from the principle of lenity, in 2015 again enters debate at the National Assembly, the adoption of a new table that sanctions more rigorously in low, medium, high and large scale , illegal possession of narcotic substances, achieving this goal with the official record No. 586 of September 14, 2015.